Implementasi Kebijakan Pemenuhan Hak Ketenagakerjaan bagi Penyandang Disabilitas di Kota Pekanbaru - Maryam Nur Arifah; Khairul Amri (Journal of Research and Development on Public Policy, 2023)
The background of this research is the decreasing attention to justice, especially justice to obtain the rights of persons with disabilities who are often considered as a group of people who have deficiencies both physically, sensory, and mentally. This treatment causes persons with disabilities to receive discriminatory treatment by society and the government. The government as one of the policy-making and policy-implementing units is expected to provide protection from the fulfillment of rights to its people. On that basis, the Provincial Government of Riau issued an Instruction to the Governor of Riau Regulation Number: 106 of 2015 concerning Instructions for Implementation of Regional Regulations of Riau Province Number. 18 of 2013 concerning the protection and empowerment of Persons with Disabilities regarding Persons with Disabilities as Other Service Providers. The purpose of this study is to examine how the employment equalization policy for persons with disabilities is implemented in Pekanbaru City and to identify aspects that impede the fulfillment of employment rights in Pekanbaru City. This study uses the theory of policy implementation by Van Meter and Van Horn along with the influencing factors. The method used in this research is a descriptive qualitative research method. With data collection techniques namely interviews observation and documentation. The results of this study indicate that the implementation of the policy of fulfilling labor rights for persons with disabilities is supported by the dimensions and objectives, resources, characteristics of implementing agencies, Communication, Disposition, Economic, social and political environment. Overall, the policies implemented by the agency have not run optimally, this can be seen from the lack of a disabled workforce working in companies. While the internal inhibiting factors are insufficient and there are not enough employees owned by the agency in carrying out the law, there is no clear punishment. Allocated for companies that violate the law and there is no clear communication between actors